A proposed model for designing an electronic system for managing patient transfer - Faramarz Pourasghar; Nesa Kavakebi (Tehran University of Medical Sciences, 2020)
Background: Information technology application in health care is increasing. The aim of  this study, is to introduce a scientific model for designing an electronic system for managing patient transfer. Materials and Methods: This study is an exploratory qualitative study. At first a review of literature was carried out for identifying clinical, managerial and process indicators necessary for patient transfer. Then 30 experts, who had vast experiences on patient transfer, were selected using purposive sampling approach and their informational needs were extracted using focus group discussion and semi-structured interviews. Then clinical indicators extracted from literature review and informational needs collected from interviews were distributed among 51 experts in the form of Delphi questionnaires. Process indicators were also distributed among 35 experts to summarize all necessary indicators for designing patient transfer system. At the final step an expert panel approved the model. Results: Thirty eight process indicators and 249 clinical and managerial components were finalized for designing the system. The process indicators were used for designing "monitoring and reports sections" of the system. The clinical indicators were used for designing "main sections" of the system including request for patient transfer, automatic algorithm for selecting destination hospital, information flow cycle, communicating clinical data and documentation. Final model also includes user interfaces relevant to responsibility of the user. Conclusion: The proposed model, which contains necessary indicators for patient transfer, can communicate clinical information among hospitals and by providing proper infrastructure, will be able to improve patient transfer process.